100 MeV/100 kW accelerator adjustment for the NSC KIPT Neutron Source physical start up - Bezditko, A.P.; Gordienko, A.N.; Gladkikh, P.I.; Gvozd, A.M.; Kapliy, D.A.; Karnaukhov, I.M.; Karnaukhov, I.I.; Lyashchenko, V.N.; Mytsykov, A.O.; Moisieienko, M.P.; Rudenko, V.E.; Ryezayev, A.V.; et al. (Вопросы атомной науки и техники, 2020)
The NSC KIPT SCA Neutron Source uses 100 MeV/100 kW electron linear accelerator as a driver for the generation of the initial neutrons. The individual State tests of the accelerator were successfully carried out in July 2018 and pilot operation of the accelerator was started in autumn 2018. Since then the following were carried out: preparation and providing of the SCA Neutron Source State Integrating tests, adjustment and improvement of the accelerator technological system performance, optimization of the electron beam parameters, preparation to the SCA Neutron Source physical start up. The main results of the accelerator operation and methods of performance im-prove are described in the paper.